Flexible photoanode on titanium foil for back-illuminated dye sensitized solar cells - Shaban, Suraya; Shafie, Suhaidi; Sulaiman, Yusran; Ahmad, Fauzan; Lokman, Muhammad Quisar; Mohamed Sharif, Noor Fadzilah (IEEE, 2018)
This paper reports the fabrication and analysis of flexible photoanode on titanium (Ti) foil for back-illuminated dye sensitized solar cells (DSSCs). Performance comparison with the solid state FTO glass based DSSC using the back-illumination and frond-illuminated techniques were also carried. During the fabrication process, the surface of Ti foil, had been treated with H2O2 and doctor blade method was applied for deposition of the photoanode on substrates. The measurement results show that the fabricated DSSC with flexible photoanode has power conversion efficiency of 1.00% under back illuminated solar radiation of 1.5 A.M while DSSCs with solid state photoanodes have power conversion efficiency of 0.53% (back-illuminated) and 2.22% (front-illuminated), respectively. The DSSC with flexible photoanode has better power conversion efficiency than the DSSC with solid-state photoanode under back-illumination condition. However, it is comparatively low from front illumination DSSC due to platinized counter electrode partially reflects light, while iodine in the electrolyte absorbs photons affects the performance.